Nitric Oxide Synthase Enzymes in the Airways of Mice Exposed to Ovalbumin: NOS2 Expression Is NOS3 Dependent - Jennifer M. Bratt; Keisha Williams; Michelle F. Rabowsky; Michael S. Last; Lisa M. Franzi; Jerold A. Last; Nicholas J. Kenyon (Hindawi Limited, 2010)
Objectives and Design. The function of the airway nitric oxide synthase (NOS) isoforms and the lung cell types responsible for its production are not fully understood. We hypothesized that NO homeostasis in the airway is important to control inflammation, which requires upregulation, of NOS2 protein expression by an NOS3-dependent mechanism. Materials or Subjects. Mice from a C57BL/6 wild-type, NOS1−/−, NOS2−/−, and NOS3−/− genotypes were used. All mice strains were systemically sensitized and exposed to filtered air or ovalbumin (OVA) aerosol for two weeks to create a subchronic model of allergen-induced airway inflammation. Methods. We measured lung function, lung lavage inflammatory and airway epithelial goblet cell count, exhaled NO, nitrate and nitrite concentration, and airway NOS1, NOS2, and NOS3 protein content. Results. Deletion of NOS1 or NOS3 increases NOS2 protein present in the airway epithelium and smooth muscle of air-exposed animals. Exposure to allergen significantly reduced the expression of NOS2 protein in the airway epithelium and smooth muscle of the NOS3−/− strain only. This reduction in NOS2 expression was not due to the replacement of epithelial cells with goblet cells as remaining epithelial cells did not express NOS2. NOS1−/− animals had significantly reduced goblet cell metaplasia compared to C57Bl/6 wt, NOS2−/−, and NOS3−/− allergen-exposed mice. Conclusion. The airway epithelial and smooth muscle cells maintain a stable airway NO concentration under noninflammatory conditions. This "homeostatic" mechanism is unable to distinguish between NOS derived from the different constitutive NOS isoforms. NOS3 is essential for the expression of NOS2 under inflammatory conditions, while NOS1 expression contributes to allergen-induced goblet cell metaplasia.